Biomedical ethics - O'Neill, Terry 1944- (San Diego, Calif. Greenhaven Press, 1999)
Presents opposing viewpoints on various issues of biomedical ethics, including animal testing, human testing, organ transplants, genetic testing, gene therapy, and cloning.
Includes bibliographical references (p. [128]-140) and index.
Keywords: Medical ethics -- Juvenile literature; Bioethics -- Juvenile literature; Medical ethics; Bioethics